Response Time as a Success in Emergency Cases in the Emergency Room at Grandmed Lubuk Pakam Hospital - Angriawan; Regula Sandra; Reisy Tane (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2025)
Response time provided by health workers in the emergency room is very helpful for patients and families because it can help reduce medical costs, but the speed and accuracy of health services provided by health workers to patients must be in accordance with standards that have been determined in accordance with the competence and abilities of medical personnel in order to guarantee in providing fast and precise emergency services. Objective: to determine the relationship between the speed of a nurse's response time and the successful handling of emergency cases in the Hospital Emergency Installation. Grandmed Lubuk Pakam. Method: This research uses a quantitative research design with a one group pretest-posttest design model, that is, before it is carried out, observations are made on the sample and after treatment, observations are made again. The data collection technique was carried out using a total sampling technique. Results: Based on the probability of the test results listed in the table, it can be seen that the resulting probability is 0.00. This means that the probability is < level of significance (? = 0.05), so that Ha is accepted and H0 is rejected. So it can be said that there is a relationship between the speed of a nurse's response time and the successful handling of emergency cases in the Hospital Emergency Room Grandmed Lubuk Pakam in 2024